2007
DOI: 10.1029/2006jd008143
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the seasonal cycle of south Asian aerosols: A regional‐scale modeling analysis

Abstract: [1] The sulfur transport and deposition model (STEM) is used to study the aerosol seasonality, distribution, and composition over south Asia from September 2004 to August 2005. Model predictions of sulfate, black carbon, primary organic carbon, other anthropogenic particulate matter, windblown mineral dusts, and sea salt are compared at two sites in south Asia where yearlong experimental observations are available from the Atmospheric Brown Cloud (ABC) project. The model predictions are able to capture both th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
104
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 46 publications
9
104
5
Order By: Relevance
“…The baseline simulation generally captures this seasonality relatively well (correlation coefficient between observed and simulated monthly mean concentrations r > 0.5 at most sites), with minimal improvement with monthly varying anthropogenic emissions. This suggests that meteorological conditions such as enhanced wet deposition during the summer monsoon period are the dominant drivers for the observed and simulated seasonal variability, consistent with other modelling studies for the same region (Adhikary et al, 2007;Moorthy et al, 2013). Model simulations where residential emissions have been switched off show that residential combustion contributes about two-thirds of simulated BC and OC at these locations.…”
Section: Model Evaluationsupporting
confidence: 73%
“…The baseline simulation generally captures this seasonality relatively well (correlation coefficient between observed and simulated monthly mean concentrations r > 0.5 at most sites), with minimal improvement with monthly varying anthropogenic emissions. This suggests that meteorological conditions such as enhanced wet deposition during the summer monsoon period are the dominant drivers for the observed and simulated seasonal variability, consistent with other modelling studies for the same region (Adhikary et al, 2007;Moorthy et al, 2013). Model simulations where residential emissions have been switched off show that residential combustion contributes about two-thirds of simulated BC and OC at these locations.…”
Section: Model Evaluationsupporting
confidence: 73%
“…With the available observations in this study the source of this nss-Ca 2+ could not be well determined. Long-range transport of soil dust, as suggested by Adhikary et al (2007) is one possibility although it is not well supported by our trajectory analysis. We discuss other possibilities, including soil derived dust from nearby islands, local sea spray containing elevated levels of Ca 2+ from erosion of coral reefs and calcareous (CaCO 3 ) plankton debris and exopolymer gels emitted from the ocean surface.…”
Section: Discussioncontrasting
confidence: 43%
“…Several studies have attributed Ca 2+ enrichment in marine aerosol and precipitation to transported crustal dust from distant continents. A model study over Indian Ocean (Adhikary et al, 2007) suggested that aerosol mass composition at Hanimadhoo during the monsoon season was dominated by mineral dust in both coarse and fine modes. The dust was transported eastwards from Africa and then brought into the Asian monsoon circulation.…”
Section: Nss-ca 2+mentioning
confidence: 99%
“…This study revealed that aerosol chemical composition is region and location specific. Therefore, region-specific and wide-range data of aerosol chemical composition are needed for better constraining model input (Adhikary et al, 2007).…”
Section: S G Aggarwal Et Al: Sources Of Organic Aerosols and Atmosmentioning
confidence: 99%
“…The chemical characterization of aerosol particles in these regions is especially important to better understand their sources, transport, and transformation, which are needed for regional models to predict aerosol distributions and effects, monsoon activity, and air quality (Adhikary et al, 2007).…”
Section: Introductionmentioning
confidence: 99%